The Incidence of Deep Vein Thrombosis in Asian Patients With Chronic Obstructive Pulmonary Disease. Issue 44 (November 2015) - Chen, Chung-Yu; Liao, Kuang-Ming
Abstract : Abstract: Most studies have focused on the prevalence of deep vein thrombosis (DVT) and pulmonary embolism in patients with chronic obstructive pulmonary disease (COPD) and acute exacerbation in Caucasian populations. DVT is supposedly less likely to occur among Asians than Caucasians, and the primary purpose of this study was to determine the actual incidence of DVT in patients with COPD in Asian populations. We enrolled patients over the age of 40 with a diagnosis of COPD (International Classification of Diseases, Ninth Revision [ICD-9]: 490–492, 496; A-code: A323 and A325) between 1998 and 2008. The index date was the date of first-time COPD diagnosis. We excluded the patients who had been diagnosed with COPD and DVT (The International Classification of Diseases, Ninth Revision, Clinical Modification [ICD-9-CM]: 453.8) before index date. The control group was frequency-matched according to age (3-year stratum), sex, and the year of admission, at a 2:1 ratio. Patients were followed from index date to when either a diagnosis of DVT was made, death occurred, December 31, 2009 was reached, or when the patients withdrew from the National Health Insurance program. The overall incidence rate of DVT was 18.78 per 10, 000 person-years in patients with COPD, and the adjusted hazard ration of DVT in patients with COPD was 1.38 (95% confidence interval 1.06–1.80), which was greater than patients without COPD after adjusting for age, sex, atrial fibrillation, hypertension, diabetes, hyperlipidemia, cerebrovascular accident, congestive heart failure, lower leg fracture or surgery, and cancer. Asian patients with COPD had a higher incidence of DVT than non-COPD patients.